MANAGEMENT AUDIT TO ASSESS THE EFFECTIVENESS OF MARKETING FUNCTION (Case Study BRITAMA Product at Kantor Cabang Bank BRI Kawi Malang) - Paramitha, Shinta Dwi (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of a management audit of the marketing function at BRI Malang Kawi is to assess the effectiveness of the implementation of the marketing function, knowing the weaknesses faced and provide recommendations or alternative improvements that can be given in an effort to increase the effectiveness of the marketing function. The method of writing of this research is descriptive method. The data were obtained by means of a case study that through questionnaires and interviews. Assessing the effectiveness of the marketing function is done by comparing the criteria, conditions, causes, and effect. The results showed that six marketing functions had assessed and had done effectively. Marketing functions that ran effectively are the marketing environment, marketing strategy, marketing organizations, marketing systems, the other marketing functions , and marketing productivity . Based on the results of the study , researchers gave some recommendations for improvement .Keywords: Management Audit, Effectiveness, Marketing Function, BRITAMA.